Genetic and Practical Classifications of Hungarian Saline Soils (Contemporary Publication) - Arany, Sándor (Acta Agraria Debreceniensis, 2002)
The first part of the paper treates possible ways of soil alkalisation and the differences due to the reaction of the medium, neutral or alkaline, respectively. Alkalisation may occur in any soil, independently of the type, or even in soil-like formations, if conditions are favorable. Alkali soils are so-called hydrogenetic formations, developed in part through water effects. Under conditions prevailing in Hungary two kinds of salt migration processes, opposite to one another, are observable, i.e.:1. Leaching downward, causing decrease in the base content of the upper layers,2. Capillary rise of salts, causing increases in base content of the upper layers.Accumulation of soluble salts usually takes place in the transition zone where these two processes get into contact with each other (Fig. 1).* A közlemény első ízben a Bukaresti Nemzetközi Talajtani Konferencián (1958. IX. 26-án) német nyelven: „Die genetische Klassifizierung der ungarischen Szikböden” címen hangzott el.As precipitation amounts in the Hungarian lowlands from 500 to 550 mm and causes leaching, true saline soils do not occur, except on some spots.Between the two extreme types – completely leached, and salinized where leaching is completely absent, respectively – there exists a long range of soils alkalised or salinized to various degrees. Thus the various types of alkali soils display an interdependence with one another as shown in Fig. 2.This interrelations may perform a base for the genetical classification of alkali soils of various properties and peculiarities. Summarising the facts stated above the paper offers a roughly, elaborated scheme for the classification of Hungarian alkali and saline soils, shown in a comprehensive table, the particulars of which are dicussed in the text. Thus the foundation is laid down for a detailed classification of alkali soils that later may become incorporated into an internationally approved system of alkali soils. The so-called practical classes of alkali soils – determined according to methods of reclamation – may be inserted into the delineated genetical system.